Effectiveness of Village Financial System Implementation (SISKEUDES) in Realizing Accountability and Transparency to Prevent Fraud - Dewila, D. (Golden Ratio of Finance Management, 2025)
This study analyzes the effectiveness of implementing the Village Financial System  (SISKEUDES) in improving accountability and transparency to prevent fraud in three villages in the Kalumpang sub-district, Mamuju district. Using mixed method research combines quantitative analysis through regression and qualitative approaches with interviews, observations, and documentation studies. The results showed that transparency significantly influenced fraud prevention (p < 0.001), while accountability also contributed, although with a more minor influence. SISKEUDES is proven to facilitate the recording and reporting of village finances, increase public trust, and reduce the potential for fund protection. However, there are still obstacles to understanding the system and technological infrastructure that need to be improved.